Influence of Extract Swiftlet Nest (Collocalia Fuciphago) as Antihyperglycemia to Circulating Endothelial Cells in Rat (Rattus novergicus) Induced by Streptozotocin - Alexandra, Francisca Diana; M, Satriyandi; Frethernety, Agnes; Triawanti, Triawanti (Fakultas Kedokteran Universitas Lambung Mangkurat, 2018)
Abstract: Hyperglycemia could increase the oxidative stress by catalyzes the formation of free radical as anion superoxide(O2-). Oxidative stress will effect in endothelial damaged. This study aimed to evaluated the influence ofÂ extract swiftlet nestÂ (Collocalia fuciphago) to glucose level andÂ CEC in rat (Rattus novergicus). Rats were classified into 4 groups, there were control group (K) and 3 treatments group (dose 1; 10 and 100 mg / kgBW) The seventh dayÂ after induced by Streptozotozin (i.p),Â the ratsÂ had increasedÂ glucose Â± 102 â 108 mg/dL, then treatedÂ with theÂ extract ofÂ Â SwiftletÂ nest for 28Â daysÂ byÂ oral.Â The CEC was measured by Hladovec method. The results showedÂ the blood glucose level were significant differences ( p = 0.035). The number of CEC decrease significantly (p=0,002). InÂ conclusion Â that extract of SwiftletÂ nest Â can effectÂ to decreaseÂ glucose level and CEC number in plasma rat (Rattus novergicus)Â Keywords: Hyperglycemia, Circulating Endothelial Cells, Collocalia fuciphago